The Use of Phonological and Semantic Strategies in Written Word Learning Among Chinese Children With Dyslexia. (November 2022) - Li, Yixun; Hui, Yi; Li, Hong; Liu, Xiangping
The present study investigated the phonological and semantic aspects of written word learning among children with dyslexia, taking into account their use of phonetic and semantic cues embedded in words. Fifty-three Mandarin-speaking fifth graders were taught the pronunciations and meanings of 24 Chinese single-character pseudowords (children with dyslexia: n = 27; age-matched peers: n = 26). The regularity of phonetic cues and the transparency of semantic cues embedded in the characters were experimentally manipulated. Children's learning outcomes in orthography-to-pronunciation associations (learning the pronunciations of novel characters) and orthography-to-meaning associations (learning the meanings of novel characters) were examined separately. Results indicated that children with dyslexia performed more poorly than did their peers only in the learning stage of orthography-to-pronunciation learning. Otherwise, children with dyslexia demonstrated comparable performance in orthography-to-meaning learning, in the use of embedded pronunciation and meaning cues, and in retention of learning in comparison with their peers. Children applied phonetic and semantic cues jointly in the learning stage. For the 1-week retention, phonetic cues supported children's performance on the task of orthography-to-pronunciation associations, whereas semantic cues aided in that of orthography-to-meaning associations. These findings expand our knowledge of children with dyslexia and provide insights for future reading interventions.